Parámetros de laboratorio para el cáncer de cabeza y cuello tratado con Nimotuzumab - Yuniet Hernández Batista; Ana María Pérez Berlanga; Gretel Hernández Pifferrer; Dayalí Teresa Rodríguez Torres (Correo Científico Médico)
RESUMEN